Impact of climate change on global food security and coping measures - Chen, Kevin Z.; Shuang, Hu (Tongfang Knowledge Network (Beijing) Technology Co., Ltd., 2024)
The threat of climate change to global food security cannot be ignored. Climate change affects all dimensions of food security, including food production, access, utilization and stability. Changing temperatures and precipitation change the water and heat conditions for plant growth, damage the physiological processes of plant development, and extreme weather events such as droughts, floods, heat waves, and hurricanes cause direct losses in food production. Changes in food supply lead to price fluctuations in the world food market. At the same time, some countries have adopted export restrictions and agricultural support policies to ensure stable domestic food supply and price stability, disrupting international agricultural product trade and exacerbating food security issues in countries that rely on agricultural product imports. Extreme weather events damage infrastructure such as transportation, logistics, energy, and communications, inhibiting the smooth flow of supply chains and reducing logistics efficiency. Food price fluctuations and income shocks brought about by climate change reduce residents' purchasing power, affect residents' food demand and utilization methods, and lead to reduced meals, fewer meals, skipped meals, less nutritious foods, and more high-fat, high-sugar, high-salt, high-energy foods to satisfy hunger. The pressure that climate change brings to people's physical and mental health has also further affected people's food consumption and nutrient intake. With the intensification of pest and disease activities and damaged transportation, food safety issues are becoming more and more worrying. In addition, climate change brings many challenges, such as violent activities, regional conflicts, forced migration, and endangered fragility and climate resilience. The stability of the food system has been impacted, exacerbating global food insecurity. The transformation of the agricultural food system is the key to responding to the climate crisis. By promoting and integrating agricultural innovation, developing climate-smart agriculture, promoting trade openness, and strengthening infrastructure and social security system construction, the climate resilience of the agricultural food system can be improved. At the same time, the role of climate finance should be brought into play, and financing channels should be actively expanded to promote the transformation of the agricultural food system and ensure global food security. JEL Codes: F316.11, S162.5